Improving the effectiveness of eradication therapy for Helicobacter pylori infection - E. A. Ljaljukova; E. N. Chernysheva (Лечащий Врач, 2024)
Background. Butyric acid (butyrate) is a short-chain fatty acid produced by anaerobic bacteria of the species Eubacterium rectale, Eubacterium ramulus, Eubacterium hallii, Roseburia cecicola, Roseburia faecis, Faecalibacterium prausnitzii and Coprococcus faecalis, as well as Fusobacteria, non-pathogenic Clostridium species, plays a key role in the physiology of the gastrointestinal epithelium. The protective effect of butyrate is realised on the part of gastric and intestinal mucosa by stimulation of anti-inflammatory and antioxidant mechanisms. Being a source of energy, it affects a wide range of cellular functions, exerting cytoprotective effect and maintaining homeostasis within the gastrointestinal tract. Butyric acid maintains the integrity of the mucosal barrier, stimulating the production of protective mucus and antimicrobial proteins, and increases the density of epithelial contacts with each other, as well as has an anti-inflammatory effect. Due to pH regulation (creates a slightly acidic environment) promotes the creation of favourable conditions for the growth of its own beneficial microbiota and unfavourable for opportunistic and pathogenic microbiota. In addition to pleiotropic effects on the human macroorganism, butyric acid and its derivatives have a direct antibacterial effect. Uric acid is able to inhibit the growth of Helicobacter pylori and have a destructive effect on the cell membrane of the microorganism, reducing cytoplasmic pH and accumulating toxic anions to prevent colonisation of Helicobacter pylori, generating hydrogen peroxide and damaging pathogenic proteins, membrane lipids and DNA of the bacterial cell.Conclusion. In Russia, as a source of butyric acid (butyrate), a preparation has been registered which, in addition to butyric acid, contains a second active component – inulin, a soluble dietary fibre, which creates a nutritious environment for the intestinal microbiota, thus stimulating the growth of beneficial bacteria and having a prebiotic effect.